(untitled) (Research, Society and Development, 2021)
The Mosqueiro-Belém do Pará region has a relationship of direct dependence on the community with the ecosystems of that region, among which, fishing is one of the main economic activities. The present work aims to evaluate the fishing of the Cajueiro community, with an emphasis on the socioeconomic aspects of the fishermen and the ethno-ecological knowledge of the species. Through semi-structured interviews, it was possible to observe that the fishing community, women are on average 36 years old, while men are 43 years old, among them 70% of the fishermen are members of the fishing colony and the work relationships are familiar, the fishing activity is developed mainly by men due to risk factors, women in turn participate mainly in shrimp fishing, reselling fish, making and repairing fishing nets. The level of education is low, with 90% with incomplete elementary school and only 10% have complete elementary school. The community uses a small boat and a gillnet. Fishermen’s knowledge of the behavior of the species caught demonstrates the relationship with the perception of seasonal changes as well as the ecological behavior of the species. This information is useful for the development of government strategies and plans in the environmental and social spectra, since a management plan is necessary for the species caught due to the intense fishing effort. As for the social, it is necessary to set goals for school development, in addition to promoting the incentive for the valorization of women in fishing.